Influence of hepatorenal syndrome on outcome of living donor liver transplantation: A single‐center experience in 357 patients. Issue 5 (19th July 2016) - Okamura, Yusuke; Hata, Koichiro; Inamoto, Osamu; Kubota, Toyonari; Hirao, Hirofumi; Tanaka, Hirokazu; Fujimoto, Yasuhiro; Ogawa, Kohei; Mori, Akira; Okajima, Hideaki; Kaido, Toshimi; Uemoto, Shinji
Abstract : Aim: Liver transplantation is the only curative treatment for hepatorenal syndrome (HRS); however, the influence of HRS on the patient and renal outcome after living donor liver transplantation (LDLT) is still unclear. The aim of the present study was to evaluate the influence of HRS on the outcome of LDLT. Methods: We retrospectively analyzed 357 consecutive adult patients who underwent primary LDLT between January 2005 and March 2013 at Kyoto University Hospital. The outcome of the patients with HRS was compared with those without HRS. Results: A total of 29 patients (8%) were diagnosed as HRS (Group‐HRS) preoperatively, and the other 328 patients (92%) were not diagnosed as HRS (Group‐Non‐HRS). Group‐HRS showed a significantly lower preoperative estimated glomerular filtration rate (22.1 vs 78.3 mL/min/1.73m 2, P  < 0.001) and higher Child–Pugh–Turcotte score (13 vs 10, P  < 0.001) than Group‐non‐HRS. After a median follow up of 60 months, the 1‐, 3‐ and 5‐year recipients' survival were 60.7%, 57.1% and 57.1% in Group‐HRS, and 83.7%, 79.4% and 76.2% in Group‐Non‐HRS, respectively ( P  = 0.030). Concomitant HRS significantly elongated postoperative hospital stays (75 vs 50 days, P  = 0.003), as well as predisposed patients to higher in‐hospital mortality (41% vs 18%, P  = 0.005). Multivariate analysis showed that preoperative renal dysfunction (estimated glomerular filtration rate on admission <40 mL/min/1.73m 2, OR 2.106, P  = 0.03) was an independent risk factor for 1‐year recipients' survival after LDLT, in addition to donor age ≥38 years (OR 3.114, P  < 0.001), Child–Pugh–Turcotte score ≥13 (OR 2.929, P  < 0.001) and left lobe graft (OR 2.225, P  = 0.004). Conclusion: Coincidence of HRS is associated with significantly worse outcome after LDLT, especially in the early post‐transplant period.